2013
DOI: 10.1039/c3cp51690c
|View full text |Cite
|
Sign up to set email alerts
|

First-principles melting of gallium clusters down to nine atoms: structural and electronic contributions to melting

Abstract: First-principles Born-Oppenheimer molecular dynamics simulations of small gallium clusters, including parallel tempering, probe the distinction between cluster and molecule in the size range of 7-12 atoms. In contrast to the larger sizes, dynamic measures of structural change at finite temperature demonstrate that Ga7 and Ga8 do not melt, suggesting a size limit to melting in gallium exists at 9 atoms. Analysis of electronic structure further supports this size limit, additionally demonstrating that a covalent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
42
1
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 44 publications
(45 citation statements)
references
References 62 publications
1
42
1
1
Order By: Relevance
“…For example, gallium clusters shows significant change in melting temperature with a change in size by one atom. [32][33][34][35][36][37] It is theoretically revealed that the property change depends on the geometric structure for gallium clusters. [32,33] In the case of metal clusters with valence electrons, such properties are not determined only by the geometric structure.…”
Section: Doi: 101002/adma201907167mentioning
confidence: 99%
“…For example, gallium clusters shows significant change in melting temperature with a change in size by one atom. [32][33][34][35][36][37] It is theoretically revealed that the property change depends on the geometric structure for gallium clusters. [32,33] In the case of metal clusters with valence electrons, such properties are not determined only by the geometric structure.…”
Section: Doi: 101002/adma201907167mentioning
confidence: 99%
“…The naked gallium clusters have been studied theoretically in order to identify the structures68 and to compare the bonding patterns to that of the bulk α‐phase, with some success 9. Bare clusters of gallium have also been investigated in order to understand the anomalous paradigm of greater‐than‐bulk melting temperatures, which have been both experimentally and theoretically confirmed 10–12. Studies of the ground‐state structure alone are manifestly unable to describe the process of melting.…”
Section: Introductionmentioning
confidence: 99%
“…How, then, does one go about identifying isomerization in a simple, straight-forward manner without a priori or "library" structural data? In the process of analyzing molecular dynamics simulations for small gallium clusters (9-36 atoms), [15][16][17] we required methods allowing for the direct comparison of structural similarity over a range of isomers, across multiple cluster sizes and temperatures, without any a priori knowledge of cluster structure. We noted similarities to the challenges encountered in the field of remote sensing image analysis, where the analysis methods typically involve a large amount of data measured under dissimilar conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Here, we present an overview of the PCA and PCC analysis techniques applied to small cluster MD, using representative examples from our simulations on small gallium clusters sized 9, 12, and 20 atoms. 15,16…”
Section: Introductionmentioning
confidence: 99%